Analisis Struktur Naratif dan Gaya Bahasa Retoris pada Novel Negeri Para Bedebah Karya Tere Liye serta Pemanfaatannya sebagai Bahan Ajar Bahasa Indonesia di SMA - Apandi, Asep; Al Gadri, Henri Henriyan; Arafat, Yasser (Jurnal Artikula, 2025)
The aim of this research is to describe the narrative structure in the novel Negeri Para Bedebah by Tere Liye, describe the rhetorical language style in the novel Negeri Para Bedebah by Tere Liye, and use the narrative structure and rhetorical language style in the novel Negeri Para Bedebah by Tere Liye as teaching materials in high school. . This research uses a qualitative descriptive type or approach, literature study methods and content analysis techniques. The steps used by researchers in collecting data are as follows: (1) outline the parts that are considered important, (2) select the data, (3) provide a description, (4) draw conclusions. The most dominant discussion result of the narrative structure in the novel Negeri Para Bedebah by Tere Liye is the orientation section, namely 149 quotations. The results of the discussion in the analysis of rhetorical language styles are dominant in the erotic language style or rhetorical questions, namely 16 quotations. The forty-eight data studied can be used as learning material for Indonesian language and literature in the independent curriculum in high school class XII. As well as the process of learning the narrative structure and language style inherent in the novel